Cannabinoids as a yield modifier in physical activit: A systematic review characters - Corrêa, Leonardo Tibiriçá; Muñoz, Juliana Weckx Peña; Faria, Beatriz do Prado Pacca; Santana, Jeferson; Yanase, Leandro; Ricci, Esther Lopes; Pantaleon, Lorena de Paula; Paula, Leonardo Ribeiro de; Ribeiro, Guilherme Mendes; Hirota, Vinicius Barroso; Fukushima, André Rinaldi (Journal of Sports Medicine and Therapy, 2021)
Marijuana is considered illicit in much of the world, and is classified as a drug for recreational use, in recent decades the medicinal use of Cannabis sativa L. has grown and diversified, being considered the only therapeutic alternative in the control of serious and incurable diseases such as syndrome of Dravet. The world panorama has shown a more liberal position, since in several countries such as the United States of America, Holland, Australia, Italy, and more recently in Canada, the use of medications, or even the recreational use of this plant, have been regulated. In this context, the investigation of the modifying effects on physical activity of empirically used cannabinoids is fundamental nowadays, mainly due to the regulatory recognition of Cannabis sativa L. as a medicinal plant in a large part of the world. Therefore, the objective of this review was to verify the evidence related to the effect of cannabis on physical performance and to identify and highlight the challenges in the interpretation of information regarding the performance of practitioners of physical activity, as well as athletes, presenting new trends in this area of research to be addressed. To carry out the systematic review, a bibliographic survey of case reports was obtained through Pubmed, Science Direct and Google Academic databases. The following keywords were used to perform the research: cannabis, performance, pain, competition. The following filters were used as inclusion criteria a languages used english; species: humans; types of articles: original articles and reviews and period of publication of articles: 1981 to 2021.